2021
DOI: 10.1371/journal.pone.0258805
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes, and practices regarding COVID-19 among pharmacists partnering with community residents: A national survey in Japan

Abstract: Background Community pharmacists play an important role in reducing COVID-19-related secondary health problems. However, the knowledge, attitudes, and practices (KAP) regarding COVID-19 among pharmacists in Japan have not yet been elucidated. Methods We conducted a web-based questionnaire survey among 1,137 pharmacists working in health support pharmacies (HSPs) in Japan. These pharmacists are responsible for providing health consultations to community residents. We assessed COVID-19-related KAP among pharma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 20 publications
3
19
0
2
Order By: Relevance
“…Previous KAP surveys of COVID-19 infection control among Japanese pharmacists reported lower KAP scores [ 23 ]. It has also been reported that the KAP scores of pharmacists were lower than those of doctors and nurses abroad [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous KAP surveys of COVID-19 infection control among Japanese pharmacists reported lower KAP scores [ 23 ]. It has also been reported that the KAP scores of pharmacists were lower than those of doctors and nurses abroad [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result of extracting the related factors of KAP using stepwise logistic regression analysis, the related factors for knowledge and attitudes scores were extracted. Regarding knowledge scores, age was extracted as in previous studies [ 23 ], with the lowest knowledge scores for the respondents in their 20s. It may be conceivable that people in their 20s have a lower risk of becoming severely ill with COVID-19, and it is thought that the percentage of pharmacy managers who manage pharmacies is small.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Guidelines were also developed at the national level by, for example, the National Health Service (NHS) in the United Kingdom [9] and by professional pharmacy organisations in Pakistan [2], Malaysia [10], South Africa [11], and the Philippines [12], to name a few. Despite these initiatives, however, several surveys have reported a general lack of access to information and training among pharmacists during the COVID-19 crisis [4,[13][14][15][16]. Furthermore, the experiences of pharmacists and pharmacy technicians during the pandemic have only been documented in a few studies.…”
Section: Introductionmentioning
confidence: 99%